Huawei-Cisco tests China's respect for property rights. - Jen Lin-Liu (IEEE spectrum)
It's been more than a year since China gained entry into the World Trade Organization (Geneva), and now the question is whether its leadership will put its mouth (and muscle) where its money is and enforce rules against piracy of intellectual property. In markets for high-tech hardware, respect for intellectual property may be slowly growing. Foreign companies and organizations like the Business Software Alliance (Washington, DC) campaign relentlessly against white-collar piracy. On this front, the most closely watched case is the one launched earlier this year in the United States by Cisco Systems Inc. (San Jose, Calif.) against a Chinese rival manufacturer of Internet routing equipment, Huawei (pronounced Hwa-way) Technologies Co. Cisco alleges that Huawei illegally copied and misappropriated software associated with Cisco networking equipment, including source code and user manuals, and infringed several Cisco patents. After months of denying any wrongdoing, Huawei admitted that an employee had copied 2 percent of the router operating software from Cisco but insisted that the company didn't know of the violation. Cisco's goal is simply to get Huawei to stop its "unlawful copying" of Cisco's intellectual property. The outcome of this court battle could have wide ramifications.